Characterization of polyherbal-incorporated polycaprolactone nanofibrous mat for biomedical applications. (July 2019) - Ramamoorthy, Rajalakshmi; Andiappan, Muthumanickkam; Muthalagu, Murugesan
The polyherbal-loaded polycaprolactone nanofibrous mat was prepared by electrospinning technique, and physical and chemical characteristics of nanofibrous mats were studied using scanning electron microscopy, x-ray diffraction, thermogravimetric analyzer, and Fourier transform infrared spectroscopy. The presence of various phytochemicals in the crude monoherbal and polyherbal extracts was analyzed. The antimicrobial activity and biocompatibility of the polyherbal-loaded nanofibrous mats were studied. The drug release pattern of the polyherbal-loaded nanofibrous mats was studied at different time intervals. The 5% drug-loaded nanofibrous mat shows higher sustainable drug release rate than 1% and 3% drug-loaded nanofibrous mats. The cell viability was found to be 98.91%, 98.77%, 98.5%, and 98.22% for polycaprolactone and 1%, 3%, and 5% for polyherbal-loaded nanofibrous mats, respectively.